A New Boundary Condition for Three-Dimensional Lattice Boltzmann Simulations of Capillary Filling in Rough Micro-Channels (Communications in Computational Physics, 2020)
A new boundary condition, aimed at inhibiting near-wall condensation effectsin lattice Boltzmann simulations of capillary flows in micro-corrugated channels,is introduced. The new boundary condition is validated against analytical solutionsfor smooth channels and demonstrated for the case of three-dimensional microflowsover randomly corrugated walls.